UJI DURABILITAS CAMPURAN AC-WC MENGGUNAKAN KOMBINASI LIMBAH PLASTIK DAN ABU CANGKANG KELAPA SAWIT - Agusmaniza, Roni; Saleh, Sofyan M.; Anggraini, Renni (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2018)
Abstract: The cause of damage and strength reduction on highway flexible pavement is the low strength and durability on the wear layer. To cope with this problem, it is necessary to add some particular additive that can increase the asphalt concrete performance. One of the additional material that can be used are plastic. Stone ash, cement and fly ash has been commonly used as a filler in asphalt mixture. But these kind of filler was hard to get and the price were relatively expensive. The palm oil shell ash wich has a specific grafity greater than asphalt is expected to be one alternative. This research aims to determine the influence of plastic waste combination substitution into the asphalt pen. 60/70 and the use of palm oil shell ash as filler on AC-WC mixture performance. The plastic used in this research is polyethylene terephthalate, polypropylene and polystyrene. The early stages of this research is to find the optimum asphalt content (OAC). After OAC obtained, then the specimens were mixed without and with the combination substitution of plastic waste as much as 2.7%; 4.7%; 6.7% against the weight of asphalt on OAC + 0.5% with and without the palm oil shell ash as a filler. The study results showed the use of plastic waste combination and the palm oil shell ash can improve the durability value. The highest value of durability obtained at 6.7% combination substitution of plastic waste, it was 111.36%, while the lowest value which found on the use of palm oil shells ash filler was 83.61%. The durability value of AC-WC mixture with and without plastic waste combination substitution had met the requirement, those were 90%, while the use of palm oil shells ash as filler does not meet the requirements.Abstrak: Penyebab kerusakan dan penurunan kekuatan perkerasan lentur jalan raya adalah rendahnya kekuatan dan keawetan di dalam lapisan aus. Untuk menanggulangi hal ini dibutuhkan suatu bahan tambah yang dapat meningkatkan lapis aspal beton. Salah satu bahan tambah yang dapat di gunakan adalah plastik. Abu batu, semen dan fly ash sudah biasa digunakan sebagai filler dalam campuran aspal. Tetapi, jenis filler tersebut susah didapatkan dan harganya relatif mahal. Abu cangkang kelapa sawit yang memiliki berat jenis lebih besar dari aspal, diharapkan dapat menjadi alternatifnya. Penelitian ini bertujuan untuk mengetahui nilai durabilitas campuran AC-WC menggunakan kombinasi limbah plastik dan abu cangkang kelapa sawit. Plastik yang digunakan pada penelitian ini adalah Polyethylene Terephthalate, Polypropylene dan Polystyrene. Tahap awal penelitian ini adalah mencari kadar aspal optimum (KAO). Setelah KAO didapat kemudian dilakukan pembuatan benda uji tanpa dan dengan substitusi kombinasi limbah plastik sebesar 2,7%; 4,7%; 6;7% terhadap berat aspal pada KAO + 0,5% tanpa dan dengan abu cangkang kelapa sawit sebagai filler. Hasil penelitian menunjukkan penggunaan kombinasi limbah plastik dapat meningkatkan nilai durabilitas. Nilai durabilitas tertinggi didapat pada substitusi kombinasi limbah plastik 6,7% yaitu 111,36% sedangkan yang terendah terdapat pada penggunaan filler abu cangkang kelapa sawit yaitu 83.61%. Nilai Durabilitas campuran AC-WC tanpa dan dengan substitusi kombinasi limbah plastik memenuhi syarat yaitu 90%, sedangkan penggunaan abu cangkang kelapa sawit sebagai filler tidak memenuhi persyaratan.